PERAN SOCIAL MEDIA MARKETING DALAM MENINGKATKAN PENJUALAN LATUSHA HIJAB PADA MASA PANDEMI COVID-19 - Nurul Khotimah, Siti; Wiranti, Ayu; Wahyuningsih, Wahyuningsih; Salsabila, Amelia; Prasetyo, Adhy (Widya Warta, 2021)
The increasing number of internet user penetration in Indonesia due to the Covid-19 pandemic with 51.1% of its activities spent on accessing social media and business trends in the fashion product sector in 2020 was seen as an opportunity by Latusha Hijab to start a business. This study aimed to know the role of social media marketing in increasing sales of Muslim fashion support products during the Covid-19 pandemic. The research was conducted by the method of observation and direct interviews with the owner of the online shop Latusha Hijab. The results showed that Latusha Hijab relied 100% on social media and internet networks in running its business. It was also known that the social media marketing implemented by Latusha Hijab was able to increase the number of sales of hijab products. However, there were still many that need to be optimized so that they could achieve sales targets.Â